2022
DOI: 10.2147/jpr.s339377
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Practices, and Perceived Barriers in Cancer Pain Management at Oncology Units: A Cross-Sectional Survey of Medical Staff in China

Abstract: Background Despite the great signs of progress in cancer pain management in China, the associated pain remains under-treated. Poor knowledge among the medical staff is an important factor contributing to the under-treatment of cancer pain. This study aimed to evaluate the knowledge, practices, and perceived barriers in cancer pain management among the medical staff at oncology units in China. Patients and Methods A cross-sectional survey was conducted with the medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, the level of awareness among healthcare workers was very high. Furthermore, respondents who had undergone training reported having more knowledge than those who hadn't (12). Our study showed that our participants had a higher awareness of the WHO analgesic ladder after the course (60.4% vs. 29.3%).…”
Section: Discussionmentioning
confidence: 57%
“…However, the level of awareness among healthcare workers was very high. Furthermore, respondents who had undergone training reported having more knowledge than those who hadn't (12). Our study showed that our participants had a higher awareness of the WHO analgesic ladder after the course (60.4% vs. 29.3%).…”
Section: Discussionmentioning
confidence: 57%
“…(2022) reported that approximately 85% of respondents claimed to have a comprehensive understanding of the three-step painkiller ladder recommended by the World Health Organization for cancer pain management. [ 11 ] In a separate study, Li et al . (2021) observed an average knowledge score of 21.56 among nurses, which surpassed the passing level.…”
Section: Search Resultsmentioning
confidence: 99%
“…(2022) found that over half of the medical staff were knowledgeable about guidelines for the treatment of cancer pain, and they reported conducting daily assessments of pain in cancer patients. [ 11 ]…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations